Answer

Verified

398.7k+ views

**Hint:**For simplifying the original equation , firstly used logarithm property

${\log _b}a = \dfrac{{{{\log }_x}a}}{{{{\log }_x}b}}$ then take base two exponential of both sides of the equation, then apply the logarithm formula ${b^{{{\log }_b}a}} = a$ to simplify the given equation .

**Formula used:**

We used logarithm properties i.e.,

${\log _b}a = \dfrac{{{{\log }_x}a}}{{{{\log }_x}b}}$

And

${b^{{{\log }_b}a}} = a$ , the logarithm function says $\log x$ is only defined when $x$ is greater than zero.

**Complete solution step by step:**

It is given that ,

${\log _2}x = {\log _4}(x + 6)$ ,

We have to solve for $x$ .

Now using logarithm property ${\log _b}a = \dfrac{{{{\log }_x}a}}{{{{\log }_x}b}}$ ,

We will get,

${\log _2}x = \dfrac{{{{\log }_2}(x + 6)}}{{{{\log }_2}(4)}}$

Now , simplify the equation , we will get the following result ,

$ \Rightarrow {\log _2}x = \dfrac{{{{\log }_2}(x + 6)}}{{{{\log }_2}{{(2)}^2}}}$ (using $\log {a^b}

= b\log a$)

$ \Rightarrow {\log _2}x = \dfrac{{{{\log }_2}(x + 6)}}{{2{{\log }_2}(2)}}$

Using ${\log _a}a = 1$ ,

$ \Rightarrow {\log _2}x = \dfrac{{{{\log }_2}(x + 6)}}{2}$

$

\Rightarrow 2{\log _2}x = {\log _2}(x + 6) \\

\Rightarrow {\log _2}{(x)^2} = {\log _2}(x + 6) \\

$ (using $\log {a^b} = b\log a$)

Now , by assuming the base of the logarithm to be $2$ ,then take the base $2$ exponential of both sides of the equation, we will get the following result ,

For equation one ,

${2^{{{\log }_2}\left( {{x^2}} \right)}} = {2^{{{\log }_2}(x + 6)}}$

By applying the logarithm formula ${b^{{{\log }_b}a}} = a$ . we will get the following result ,

${x^2} = x + 6$

Or

${x^2} - x - 6 = 0$

$

\Rightarrow {x^2} - 3x + 2x - 6 = 0 \\

\Rightarrow x(x - 3) + 2(x - 3) = 0 \\

\Rightarrow (x + 2)(x - 3) = 0 \\

\Rightarrow x = - 2 \\

and \\

x = 3 \\

$

Now recall that the logarithm function says $\log x$ is only defined when $x$is greater than zero.

Therefore, in our original equation ${\log _2}x = {\log _4}(x + 6)$ ,

Here,

$

(x) > 0 \\

and \\

(x + 6) > 0 \\

$ ,

When $x = - 2$ , it is less than zero.

Therefore , we reject $x = - 2$ .

And when $x = 3$ , it is greater than zero .

**Therefore, we have our solutions i.e., $x = 3$ .**

**Note:**The logarithm function says $\log x$ is only defined when $x$ is greater than zero. While defining logarithm function one should remember that the base of the log must be a positive real number and not equals to one . At the end we must recall that the logarithm function says $\log x$ is only defined when $x$ is greater than zero. While performing logarithm properties we have to remember certain conditions , our end result must satisfy the domain of that logarithm .

Recently Updated Pages

How many sigma and pi bonds are present in HCequiv class 11 chemistry CBSE

Mark and label the given geoinformation on the outline class 11 social science CBSE

When people say No pun intended what does that mea class 8 english CBSE

Name the states which share their boundary with Indias class 9 social science CBSE

Give an account of the Northern Plains of India class 9 social science CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

Trending doubts

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE

Difference Between Plant Cell and Animal Cell

Which are the Top 10 Largest Countries of the World?

10 examples of evaporation in daily life with explanations

Give 10 examples for herbs , shrubs , climbers , creepers

Write a letter to the principal requesting him to grant class 10 english CBSE

Change the following sentences into negative and interrogative class 10 english CBSE